RFID (NFC) application employment on inventory tracking to improve security / Muhammad Mikail Mohd Efendy Goon - Mohd Efendy Goon, Muhammad Mikail (2014)
The possibility of getting product identity from being stolen is likely to happen whre and the replication of the product will be made from third parties and it will almost book the same as the original version. The introduction of new technology in security enforcement for product which is RFID called Radio Frequency Identification that can scan and detect the details of the product much easier without the need any line of sight unlike barcodes system being used nowadays.